Genetic relationship between Kadazans and fifteen other Southeast Asian races - Tan, Soon Guan (Universiti Pertanian Malaysia, 1979)
Genetic distance analysis based on five polymorphic biochemical genetic markers was done to determine the genetic distance between Kadazans and fifteen other races living in Southeast Asia. Kadazans were found to he closer to Iban, Paiwan, Visayan, Ifugao, Atyal, Aboriginal ilialays, Land Dayah, Tagalog and Southern Chinese titan they are to Bataks, Senoi, Bunun,malays, Aetas and Southern Indians. Gene frequency comparisons for several new biochemical genetic markers such as soluble glutamate pyruvate transaminase, glyoxalase I and esterase D were made between Kadazans and those few Southeast Asian races 'which had been analysed for these new marhers. In case of those markers in which no data is available for other Southeast Asian races, the Kadazan gene frequencies 'were compared to those of races found elsewhere in the world,